(untitled) (PETITUM, 2023)
ABSTRACT: The research aims: 1) To understand restorative justice legal provisions for narcotics crimes. 2) To understand the effectiveness of drug abuse rehabilitation. The research was conducted using empirical juridical methods. Researching restorative justice legal provisions for narcotics crimes and empirically examining the effectiveness of rehabilitation for narcotics abuse in the investigation process. The research results show: 1) perpetrators of narcotics crimes such as addicts or victims of narcotics abuse can be resolved through restorative justice by getting the opportunity to undergo medical or social rehabilitation without having to wait for the court results. 2) Knowing how restorative justice is applied to perpetrators of narcotics crimes at the investigation stage through an Integrated Assessment carried out by the Integrated Assessment Team. Apart from that, it is also to find out what obstacles investigators face in implementing restorative justice against perpetrators of narcotics crimes. ABSTRAK: Penelitian bertujuan: 1) Untuk memahami ketentuan hukum restoratif Justice terhadap tindak pidana narkotika. 2) Untuk memahami efektifitas rehabilitasi penyalahgunaan narkotika. Penelitian dilakukan dengan menggunakan metode Juridis empiris. Meneliti terkait ketentuan hukum restoratif justice terhadap tindak pidana narkotika dan secara empiris meneliti efektifitas rehabilitasi terhadap penyalahgunaan narkotika dalam proses penyidikan. Hasil penelitian menunjukan: 1) pelaku tindak pidana narkotika seperti pecandu atau korban penyalahgunaan narkotika dapat di selesaikan melalui restoratif justice dengan mendapatkan kesempatan untuk di lakukan rehabilitasi medis atau pun sosial tanpa harus menunggu hasil pengadilan. 2) Mengetahui bagaimana penerapan Restoratif justice yang di berlakukan terhadap pelaku tindak pidana narkotika pada tahap penyidikan melalui Assesment Terpadu yang di lakukan oleh tim aseesment Terpadu selain itu juga untuk mengetahui apa saja kendala yang di hadapi penyidik dalam menerapkan restoratif justice terhadap pelaku tindak pidana penyalahgunaan narkotika.